ISOLATION OF CRYSTALLITE ANATASE AND RUTILE FROM TiO2 P25 FOR DYE SENSITIZED SOLAR CELL - , IRFAN ILMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The isolation of crystallite anatase and rutile from commercial TiO2 P25 Degussa was carried out. The aim of this research was to study the potential of pure anatase and rutile based Dye Sensitized Solar Cell (DSSC) for the development of industrial DSSC. The crystal phase, crystal size and crystal shape of TiO2 P25, isolated anatase and isolated rutile were characterized by X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). DSSC parameters including Fill Factor (FF), Current Short Density (Jsc) and Open Voltage (Voc) were determined to calculate the cell efficiency from I-V test using ruthenium-N719 sensitized cell test. Crystallite Anatase was isolated by dissolving TiO2 P25 powder in ammonia and hydrogen peroxide solution for 15 hours followed by washing and drying. Whereas the isolation of rutile was done by dissolving P25 in hydrofluoric acid solution for 24 hours followed by washing and drying. DSSC cell performances of the isolated anatase, isolated rutile and original P25 photoanodes were measured. The I-V curves were measured under 100 mW /cm2 Xe lamp with active area of 1.5 cm2. Pure anatase and rutile were successfully isolated with the percent yield of 35% and 25.6% respectively. X-ray diffraction pattern showed obviously that no rutile contaminant in the resulted anatase and vice versa. TEM image shows characteristic crystallite anatase and crystallite rutile with the particle size of 21 nm and 40 nm. Surface area measurement exhibits that surface area of isolated anatase was 64.7m2/g slightly higher than that of P25. Whereas, surface area of isolated rutile was 33.17m2/g slightly lower than that of P25. Study of crystal transformation of anatase to rutile showed that isolated anatase is more stable than that of P25. The evaluation of DSSC performance shows that the DSSC efficiency of anatase (0.79%) and rutile (0.55%) based cell are higher than that of P25 (0.51%) based cell